Kombinirano daljinsko ogrevanje in hlajenje v mestu Gera (Nemčija) s tehnologijo parnih kotlov - Noeres, Peter (Strojniški vestnik, 2000)
The paper introduces steam-jet ejector technology and its use in a pilot project of Energieversorgung Gera Gmbh in Germany(funded by the German Ministry of Science and Education). Within this project a chiller plant with a steam-jet ejector chiller unit and a compression chiller supplies a district cooling network in downtown Gera Germany. The technical concept of the chiller plant, performance characteristics of the steam-jet ejector, previous operational experiences and future areas of application will be described.
Keywords: ogrevanje daljinsko; hlajenje daljinsko; ejektorji parni; stroški obratovalni; daljinsko ogrevanje; hlajenje; hladilni sistemi; parni kotli